1997
DOI: 10.1152/ajpregu.1997.273.1.r100
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin enhances cardiac performance in antarctic icefish species that express the protein

Abstract: Channichthyid icefishes of Antarctica are unique among adult vertebrates. All icefish species lack hemoglobin and red blood cells in their circulating blood. All icefishes examined to date also lack the intracellular oxygen-binding protein myoglobin (Mb) in their oxidative skeletal muscles. However, some icefish species do express Mb in their heart ventricles. It is unknown whether Mb in those species in which it is present represents an evolutionary relic or has functional significance. To address this proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…Overall the results showed that perfused Mb-rich hearts were better at maintaining O 2 consumption and cardiac performance under hypoxic conditions than Mb-poor hearts [56,63]. Similar results were obtained when comparing the mechanical performance of perfused hearts from two icefish species -one expressing and one not expressing Mb protein [65]. Thus it appears that heart Mb plays a corresponding role in fish as in mammals, namely in maintaining O 2 consumption in myocytes when O 2 levels decrease.…”
Section: Mammalssupporting
confidence: 54%
“…Overall the results showed that perfused Mb-rich hearts were better at maintaining O 2 consumption and cardiac performance under hypoxic conditions than Mb-poor hearts [56,63]. Similar results were obtained when comparing the mechanical performance of perfused hearts from two icefish species -one expressing and one not expressing Mb protein [65]. Thus it appears that heart Mb plays a corresponding role in fish as in mammals, namely in maintaining O 2 consumption in myocytes when O 2 levels decrease.…”
Section: Mammalssupporting
confidence: 54%
“…Some species lack cardiac myoglobin as well. The mechanical performance of isolated perfused hearts from two very similar, congeneric channichthyids show little difference at normal work loads, but that of the species with myoglobin is far more able to maintain cardiac output in the face of the additional insult of increased aortic arterial pressure (Acierno et al, 1997;Sidell, 1998). Channichthyid fish without myoglobin served as a control of the effects of nitrite in an experiment demonstrating decreased cardiac function following blockade of cardiac myoglobin (Acierno et al, 1997).…”
Section: Fish Without Myoglobinmentioning
confidence: 99%
“…When isolated, perfused hearts from Mb-expressing and Mb-lacking icefish species are challenged with increasing afterload, hearts whose ventricles contain Mb are capable of greater pressure-work (Acierno et al, 1997). Furthermore, specific poisoning of Mb function in these preparations causes performance of Mb-expressing hearts to decrement below that of normally Mb-lacking hearts, indicating that the latter display mechanisms that partially compensate for the absence of this oxygen-binding protein.…”
Section: Discussionmentioning
confidence: 99%